Teachers' Views on Values Education: Case of Afyonkarahisar Province - Hakan Bayırlı; Okan Doruk; Aysel Tüfekci (Anı Publishing, 2020)
The aim of the current study is to reveal the experiences and opinions of the teachers working in various branches in Turkey on the implementation of the values education project. The research was conducted in a basic qualitative research design. Typical case, snowball and maximum variation sampling techniques were used to select the participants. In this respect, the participants were 10 teachers working in different branches and participating in the values education project. Research data were obtained through semi-structured interview and were analyzed by content analysis. The transcripts were read repeatedly and coded. Then, the codes obtained were reviewed and categories were formed. Finally, the related categories were grouped under themes. The study reveal that teachers deemed values education necessary due to the changes in our society and culture, and that teachers mostly used inculcation and action learning approaches during values education and stated that value education activities had a positive effect on the students. In addition, it was seen that the teachers thought that the use of rewards during the teaching of value would have a negative effect on the students. It may be suggested to take measures to increase teachers' interest in values education.